The Concept of Human Perfection as Viewed by Ibn Sina and Ibn Arabi - Ali Sohbatlo (حکمت سینوی)
The question of human perfection and the perfect human is a subject of attention for all religions and philosophical, ethical, and educational schools of thought. The ultimate perfection is a level of human existence in which all innate, spiritual, and human potentials are actualized through spiritual practice. The main goal of this research is to examine human perfection from the perspectives of Ibn Sina and Ibn Arabi. A comparative method has been used to achieve this goal. In Ibn Sina's epistemological approach, only rational intuition is applicable, and it is not possible to speak of mystical knowledge and heart intuition. Ibn Sina considered the ultimate goal of knowledge and happiness to be rational and cognitive understanding, and connection to the Active Intellect, which is based on theoretical reason and rational intuition. However, in Ibn Arabi's intellectual system, every being is ontologically a manifestation of the name or names of God, and epistemologically, their understanding of God depends on their ability to receive divine manifestations. In Ibn Arabi's epistemological and intellectual system, the higher truths are received with the help of discovery and intuition and are of the nature of presentational knowledge. In Ibn Arabi's epistemological and intellectual system, human perfection is depicted based on love and discovery and intuition. Therefore, the perfect human of Ibn Sina, in his rational-intuitive perfection, is consistent with the mystical perfect human of Ibn Arabi. Therefore, the perfection of theoretical reason within the Peripatetic framework is a connection to practical reason and is incomplete without it. In both viewpoints, it is stated that humans have different levels of perfection. Acquiring these levels is gradual, and after going through this process of gradual perfection and ascending the levels of perfection, a human finally reaches the lofty position of his ultimate perfection. A review of Ibn Arabi's religious and mystical texts shows that he was by no means separate from society but was rather within it and considered the isolation of mystics and shunning society to be wrong. The perfect human of Ibn Sina, in a philosophical-mystical view, is the same as the mystical perfect human of Ibn Arabi and has no superiority over the perfect human of mystics. Therefore, it is not only the perfect human of Ibn Sina who is closer to the human of Islam and the Quran, but also the mystical perfect human of divine mystics, due to his complete manifestation of God, is the same as the Quranic and Islamic perfect human.